Association of Childhood Asthma Control Test and Asthma Control Test with Airway Hyper-responsiveness in Children and Adolescents - Terence Ting-Hei Yeung; Shuk-Yu Leung; Andy Cheuk-Ting Hou; Eric Yat-Tung Chan; Ka-Li Kwok (Pediatric Respirology and Critical Care Medicine)
Introduction: We aimed to investigate the association of childhood asthma control test (CACT) and asthma control test (ACT) with airway hyper-responsiveness (AHR) defined by the methacholine challenge test in asthmatic children and adolescents. Materials and Methods: This study was a retrospective analysis of a hospital-based cohort. Each subject has completed the CACT or ACT, spirometry, and methacholine challenge test. A CACT or ACT score of 20 or above was defined as symptoms controlled. AHR was defined by a positive methacholine challenge test. Results: A total of 101 asthmatic children and adolescents were included. There was no statistically significant difference in the proportion of subjects with controlled or uncontrolled symptoms defined by CACT or ACT when compared to AHR defined by the methacholine challenge test. If a negative methacholine challenge test was regarded as a gold standard to define controlled “AHR,” CACT and ACT had a sensitivity of 0%, specificity of 94.4%, positive predictive value of 0%, and negative predictive value of 68.1% to detect controlled subjects in our sample. Conclusion: In this study, CACT or ACT did not correlate well with AHR defined by the methacholine challenge test. CACT or ACT alone may not be comprehensive enough to detect subclinical hyperactive airways in children and adolescents.